A Practical Guide to Presacral Masses: Imaging Characteristics and a Proposed Classification System - Muthu Purushothaman, Selvaganesan; Ananthakrishnan, Ramesh (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The presacral space is an anatomically intricate region that can host a wide spectrum of pathologies ranging from benign developmental cysts to aggressive malignancies. Due to the rarity and diverse etiology of presacral masses, their diagnosis and management remain a significant challenge necessitating a multidisciplinary approach. This article provides a comprehensive review of the imaging features, classification, and management strategies for presacral masses. An imaging-based classification system is proposed, grouping the lesions into benign and malignant based on aggressive imaging features such as irregular margins, bone erosion, and pelvic sidewall invasion. Additionally, surgical approaches tailored to lesion characteristics and anatomical extent are discussed. This review article aims to aid radiologists in the effective diagnosis of presacral lesions.
Keywords: presacral masses; presacral space; presacral masses radiology; radiological classification